POTEHI IN NEW ORDER’S RESTRAINT: THE LOST OF INHERITOR GENERATION OF CHINESE WAYANG CULTURE - Kurniawan, Hendra (International Journal of Humanity Studies (IJHS), 2017)
This article aimed to describe the history of wayang potehi development in Indonesia especially during the New Order period that became a dark time for its development. This study used historical research methods including heuristic step or source searching, source critics, data interpretation, and historiography or historical writing. The results showed that wayang potehi began to develop in Indonesia as the coming of Chinese immigrants around the 17th century and experienced acculturation with local culture. Wayang potehi experienced dark times when emerged the discriminatory rule of the New Order government against all things related to Chinese culture. The restraint to freedom of expression and preservation of wayang potehi cut off the chain of inheritor generation.DOI: https://doi.org/10.24071/ijhs.2017.010105